Energy optimised resource scheduling algorithm for private cloud computing. (2016) - Goyal, Sudhir; Bawa, Seema; Singh, Bhupinder
In universities, IT infrastructure is usually non-centralised. Setting up a private cloud setup in academic institutes has an edge over the traditional approach of IT infrastructure distribution to its various departments, schools and centres etc. This work proposes a energy efficient resource management solution specially designed for small and medium sized Infrastructure as a Service (IaaS) cloud in Universities. The proposed algorithm optimises the energy consumption through efficient resource scheduling, virtual machine (VM) consolidation and VM admission control policies. Proposed algorithm has been evaluated by keeping in consideration the number of accepted incoming VM requests and energy consumption of cloud infrastructure. Experimental results reveal that proposed algorithm enhances the acceptance rate of VM requests with the reduction of overall energy consumption of cloud infrastructure.